Can a Patent Be Granted for an AI-Generated Invention?. Issue 11 (15th September 2020) - Engel, Andreas
Abstract: Three patent offices had to answer the question of whether a patent can be granted for an invention for which an Artificial Intelligence (AI) system called DABUS was named as inventor. All applications were dismissed, but for different reasons. While the European Patent Office focused on formal rules, the UK Intellectual Property Office considered more substantive aspects, and the US Patent and Trademark Office relied on statutory language. From a policy perspective, the decisions find support in the fact that there is no clear consensus for AI to be recognized as an inventor, and that difficult questions would ensue if this were accepted. From a doctrinal perspective, the decisions do not rule out the patentability of AI-assisted inventions in general, as it remains possible to designate a human inventor when AI has merely facilitated the inventive process. This leaves the question of who should own a patent for an AI-generated invention, if patentability for such inventions is considered desirable. A possible solution could be to grant ownership directly to the company operating or owning the AI.